Seeing anew: the role of student leadership in professional learning. Issue 4 (7th August 2020) - Hill, Stephanie
ABSTRACT: The growing interest in the role of student agency within schools, as well as the need for effective professional learning, supports further investigation into initiatives aiming to develop meaningful and sustainable student involvement in school improvement approaches. This article explores the role of student leadership in professional learning approaches that aim to improve learning through collaborative reflection on teaching practice. It provides a review of literature that investigates student involvement in professional learning, specifically through the development of student voice and the inclusion of students as co-researchers in school improvement initiatives. Following this, the article draws on the findings from a case study that examined the role of a Student Learning Community (SLC) in professional learning and presents an overview of current practice where students are involved in a research approach to professional learning called a Best Practice review. The insights drawn from the case study and practice example, both situated in a secondary school in England, offer considerations for educators wishing to explore and/or introduce student leadership approaches to professional learning, as well as recommendations for further study into the role of students as agents in school improvement initiatives.